2012
DOI: 10.1089/end.2011.0418
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Warm-up Exercises Improve Performance of Senior-Level Trainees During Laparoscopic Renal Surgery

Abstract: Background and Purpose: Surgery is a high-stakes ''performance.'' Yet, unlike athletes or musicians, surgeons do not engage in routine ''warm-up'' exercises before ''performing'' in the operating room. We study the impact of a preoperative warm-up exercise routine (POWER) on surgeon performance during laparoscopic surgery. Materials and Methods: Serving as their own controls, each subject performed two pairs of laparoscopic cases, each pair consisting of one case with POWER ( + POWER) and one without (-POWER).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 16 publications
0
92
1
Order By: Relevance
“…Two cross-over trials [27,29] reported ambiguous findings for the effect of preoperative simulation on surgical performance; the first study [27] reported a significant effect as measured by one global rating scale, but no effect according to another also-reported scale. The second study [28] found a significant improvement in one assessed task, but not another. One RCT [22] and one cross-over trial [30] found that preoperative simulation had no effect on subsequent performance, as judged by a global rating scale.…”
Section: Studies Reporting Global Rating Scorementioning
confidence: 84%
See 4 more Smart Citations
“…Two cross-over trials [27,29] reported ambiguous findings for the effect of preoperative simulation on surgical performance; the first study [27] reported a significant effect as measured by one global rating scale, but no effect according to another also-reported scale. The second study [28] found a significant improvement in one assessed task, but not another. One RCT [22] and one cross-over trial [30] found that preoperative simulation had no effect on subsequent performance, as judged by a global rating scale.…”
Section: Studies Reporting Global Rating Scorementioning
confidence: 84%
“…The authors reported undertaking structured mental practice significantly improved participants' mental imagery of a procedure. Finally, in one cross-over study [28] it was found that preoperative simulation improved attention, reduced distraction / drowsiness and reduced mental workload in comparison to no warm-up.…”
Section: The Warm-up Tasksmentioning
confidence: 97%
See 3 more Smart Citations